A neutrinophilic 2HDM as a UV completion for the inverse seesaw mechanism - Enrico Bertuzzo; Pedro A. N. Machado; Zahra Tabrizi; Renata Zukanovich Funchal (Journal of High Energy Physics, 2017)
Abstract In Neutrinophilic Two Higgs Doublet Models, Dirac neutrino masses are obtained by forbidding a Majorana mass term for the right-handed neutrinos via a symmetry. We study a variation of such models in which that symmetry is taken to be a local U(1), leading naturally to the typical Lagrangian of the inverse seesaw scenario. The presence of a new gauge boson and of an extended scalar sector result in a rich phenomenology, including modifications to Z, Higgs and kaon decays as well as to electroweak precision parameters, and a pseudoscalar associated to the breaking of lepton number.